The quality of chief integrity officer and ethical climate on the level of ethics and integrity and its relationship with organizational commitment : the case of federal government sector - Asmawati, Sajari (2019)
The effectiveness of the implementation of ethics and integrity is very important in reducing the ethical scandals such as corruption, bribery, fraud, governance inefficiency and poor internal control. Based on the statistics reported by the Malaysian AntiCorruption Commission (MACC), it shows that civil servants are the most involved group in the ethical scandals starting from the top management until the lower staff in the publicsector organization. The objectives of the study are to examine the relationship of the three dimensions of the quality of Chief Integrity Officer (independence, competence, work performance) and ethical climate with the level of ethics and integrity in Malaysian public-sector organization, and the relationship of the level of ethics and integrity with organizational commitment (affective, continuance, normative). Out of 128 questionnaires that were emailed to CIOs in in the Federal level, 83 questionnaires were received and used to analyse the hypotheses. Based on the Multiple regression, the results of this study showed that the two dimensions of the quality of CIO (competence, work performance) and ethical climate have a significant and positive relationship to level ethics and integrity. Meanwhile, the relationship between the level of ethics and integrity with organization commitment was found to have a significant and positive relationship with affective commitment. However, level of ethics and integrity was not found to have significant relationship with continuance and normative commitment. It shows that level of ethics and integrity is not influenced by continuance and normative commitment in the organization. Thus, this study suggests that a higher CIO quality i.e. competence, work performance and ethical climate, can enhance the level of ethics and integrity of the public sector in Malaysia. This study showed that the government efforts in the implementation of the national integrity agenda was effective as the level of integrity at Malaysian public sector is currently at 79%. To increase the competency level of the CIO, it is highly advisable for them to enrol in more professional courses related to ethics and integrity. CIOs should also perform their roles such as coordinating and monitoring programs and reporting any breaches of integrity without fear or favour. To increase or improve existing ethical climate, the organization should establish clear policies, guidelines and of conducts to all employees with ethical and integrity in the government ministries, departments and statutory bodies in the public sectors. Management should portray that their organization truly cares on this matter as this would help to improve organisational commitment effectively.